Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-42476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Turbulent Flow Characteristics and Coherent Vortices on the Pressure Recovery of Annular Diffusers: Part A — Experimental Results

Abstract: Exhaust diffusers downstream of turbines are used to transform the kinetic energy of the flow into static pressure. The static pressure at the turbine outlet is thus decreased by the diffuser, which in turn increases the technical work as well as the efficiency of the turbine significantly. Consequently, diffuser designs aim to achieve high pressure recovery at a wide range of operating points. Current diffuser design is based on conservative design charts, developed for laminar, uniform, axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…By resolving the turbulent flow scales, the anisotropic character of the flow is also resolved. It has been shown that the calculated Reynolds shear stresses and the resulting pressure recovery of the annular diffuser follow the correlation presented by [8].…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…By resolving the turbulent flow scales, the anisotropic character of the flow is also resolved. It has been shown that the calculated Reynolds shear stresses and the resulting pressure recovery of the annular diffuser follow the correlation presented by [8].…”
Section: Introductionsupporting
confidence: 69%
“…Furthermore, they came to the conclusion that the Reynolds stresses of the rotor outflow at the blade tip are anisotropic. Based on these findings, Kuschel et al [8] presented a correlation between the Reynolds shear stresses at the blade tip region of the rotor outflow and the pressure recovery in the two examined annular diffusers (see Fig. 1).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Kuschel and Seume (2011) conducted additional experiments using a NACA profile instead of cylindrical spokes. A detailed analysis of these experimental results can be found in Kuschel et al (2015) and Drechsel et al (2015). They conclude that the increase in pressure recovery is caused by the interaction of tip vortices of the rotor blades with the diffuser boundary layer.…”
Section: Stabilisation Numbermentioning
confidence: 91%